VAWT cluster parameter study on overall cluster performance - Silva, Jeffrey E.
The effect of the windward turbines in a clustered wind farm has significant effects on the performance of the downwind turbines which are characterized by velocity deficit and turbulence intensity. Various published literatures concluded that for some cases the effect of the turbine wakes in VAWT clustered configuration increases the overall performance of the clustered wind farm. In this study, the effect of varying equivalent rotor diameter spacing, varying internal angles and direction of rotations in a clustered wind turbine configuration were investigated. There was an increase of 8.91% in a clustered turbine arrangement with 2 equivalent rotor diameter spacing and 60 degrees oblique angle compared to an isolated turbine. Meanwhile, there was no detectable increase to the performance of clustered turbine arrangement of 12 rotor diameter spacing. There was a significant improvement to the performance of the upwind turbine and to the overall cluster performance when the cluster tends to form a straight line perpendicular to the flow of the free-stream wind. On the other hand, both the average coefficient of performances and individual turbine performances of "mirror images" cluster pairs were found to have no significant variation in the different combination of turbine rotations studied in the CFD simulation.